Chitosan-film enhanced chitosan nerve guides for long-distance regeneration of peripheral nerves. (January 2016) - Meyer, Cora; Stenberg, Lena; Gonzalez-Perez, Francisco; Wrobel, Sandra; Ronchi, Giulia; Udina, Esther; Suganuma, Seigo; Geuna, Stefano; Navarro, Xavier; Dahlin, Lars B.; Grothe, Claudia; Haastert-Talini, Kirsten
Abstract: Biosynthetic nerve grafts are developed in order to complement or replace autologous nerve grafts for peripheral nerve reconstruction. Artificial nerve guides currently approved for clinical use are not widely applied in reconstructive surgery as they still have limitations especially when it comes to critical distance repair. Here we report a comprehensive analysis of fine-tuned chitosan nerve guides (CNGs) enhanced by introduction of a longitudinal chitosan film to reconstruct critical length 15 mm sciatic nerve defects in adult healthy Wistar or diabetic Goto-Kakizaki rats. Short and long term investigations demonstrated that the CNGs enhanced by the guiding structure of the introduced chitosan film significantly improved functional and morphological results of nerve regeneration in comparison to simple hollow CNGs. Importantly, this was detectable both in healthy and in diabetic rats (short term) and the regeneration outcome almost reached the outcome after autologous nerve grafting (long term). Hollow CNGs provide properties likely leading to a wider clinical acceptance than other artificial nerve guides and their performance can be increased by simple introduction of a chitosan film with the same advantageous properties. Therefore, the chitosan film enhanced CNGs represent a new generation medical device for peripheral nerve reconstruction.